Comparative study of nosZI and nosZII clade isolates: insights into their responses to environmental variables and soil fertilization types - Li, Haoran; Luo, Qishi; Sun, Lichao; Xu, Huicui; Hao, Xiaodong; Zhu, Kai; Li, Ming; Li, Bao; Jiao, Wei; Geng, Jibiao; Chen, Zhiqun; Huang, Lihua; et al. (Frontiers in Plant Science, 2025)
IntroductionSoil nitrous oxide (N2O) emissions are a major contributor to global warming and climate change. Microbial N2O reduction via the nosZ gene—classified into clade I and clade II—is the only known biological sink for N2O.MethodsIn this study, we isolated two N2O-reducing bacterial strains: an Enterobacter sp. harboring nosZ clade I (nosZI) and a Pseudomonas sp. harboring nosZ clade II (nosZII). We evaluated their performance under different environmental conditions and their effects on N2O emissions from agricultural soils subjected to varying fertilization strategies.ResultsPure culture experiments revealed that growth and N2O-reducing activity in both strains were significantly influenced by pH, oxygen concentration, nitrate levels, and carbon source. Notably, the nosZII strain demonstrated broader environmental adaptability and higher N2O-reduction efficiency across a range of conditions. In soil microcosm experiments, N2O emissions were strongly affected by fertilization type, with mixed organic-inorganic treatments producing the highest emissions. Inoculation with the nosZII strain significantly reduced N2O emissions in soils receiving inorganic or combined fertilizers. In contrast, the nosZI strain tended to increase emissions, except under the mixed fertilization regime.DiscussionThese findings highlight the importance of selecting N2O-reducing microbial strains based on their functional capacity and environmental tolerance. This work advances the development of targeted microbial strategies for mitigating N2O emissions, supporting more sustainable and climate-resilient agricultural practices.